Microsurgical reconstruction for devastating brachial plexus injuries - PS Bhandari; LP Sadhotra; P Bhargava; AS Bath; Prakash Singh; MK Mukherji (The Indian Journal of Neurotrauma, 2005)
Forty-four patients with brachial plexus injuries were treated in the period between Jun 1999 and Nov 2004. The ages of these patients ranged from 15 to 57 years (average 26 yrs). Most of the cases (72%) were caused by high velocity motor vehicle accidents. Gunshot and splinter injuries, direct hit from a motor vehicle (pedestrians), fall from height were responsible for rest of the cases (28%). Associated skeletal and vascular injuries were present in 43% of cases. The denervation time ranged from 4 months to 11 months. Majority of the patients had injuries in the upper brachial plexus involving C5, C6 & C7 roots. Global palsy was present in 8 cases. Reconstructive procedures included microneurolysis in 13 cases, nerve grafting in 7 and neurotization in 24 cases. Motors for neurotization included accessory nerve, inter-costal nerves, phrenic nerve, ulnar nerve fascicles and motor branch of radial nerve to triceps. Useful results were obtained in 64% of cases. Almost all patients had pain relief following surgery. In none of the case results worsened after surgery. Microsurgical techniques can obtain gratifying results in traumatic lesions of brachial plexus, provided surgical intervention is undertaken at an early stage.